2018
DOI: 10.1002/jcla.22695
|View full text |Cite
|
Sign up to set email alerts
|

The association between albumin‐dNLR score and disease activity in patients with rheumatoid arthritis

Abstract: Background Recently, clinical studies have described an association between albumin and the derived neutrophil to lymphocyte ratio (dNLR) with several diseases. This study was aimed to investigate the albumin‐dNLR (ALB‐dNLR) score in rheumatoid arthritis (RA) patients and assess its relationship with clinical and laboratory parameters of RA. Methods We retrospectively enrolled 127 RA patients, 155 osteoarthritis (OA) patients, and 155 healthy controls. The ALB‐dNLR score was based on serum albumin level, neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Combination of albumin concentration with dNLR in one index (albumin-dNLR score) was speculated to be a valuable biomarker to reflect inflammatory status in gastric cancer [36], pancreatic cancer [37], and RA [14]. We observed a higher albumin-dNLR score in our RA patients compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Combination of albumin concentration with dNLR in one index (albumin-dNLR score) was speculated to be a valuable biomarker to reflect inflammatory status in gastric cancer [36], pancreatic cancer [37], and RA [14]. We observed a higher albumin-dNLR score in our RA patients compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 52%
“…To best of our knowledge, only one retrospective study reported the association of albumin-dNLR score with disease activity parameters among their RA patients [14]. Moreover, they suggested that it can enhance the efficacy of RA diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, apart from NLR and PLR, new blood-cell-derived indexes, such as the derived NLR (dNLR) [ 26 ] and the lymphocyte to monocyte ratio (LMR) [ 17 ] have gained interest in recent years, as potential diagnostic tools in RA. Conversely, no data are available about the performance of the systemic inflammation response index (SIRI) and the aggregate inflammation systemic index (AISI) in RA.…”
Section: Introductionmentioning
confidence: 99%